Peran Guru Bimbingan Konseling dalam Memotivasi Santri Kelas VII MTsS Yati Kamang Mudik melalui Kurikulum Merdeka Belajar - Nurmawarni Siregar; Muhiddinur Kamal (Departement of Mathematics Education, 2024)
The problem studied in this research is, what is the role of guidance and counseling teachers in motivating class VII students at MTS Yati Kamang Mudik. The aim of this research is to determine the role of guidance and counseling teachers in motivating class VII students at MTs Yati Kamang Mudiak through the Independent Learning Curriculum. This research uses descriptive qualitative methods with data collection techniques by means of observation and interviews. Data analysis techniques using Miles and Huberman theory were used, namely data presentation, drawing conclusions, and data reduction. With interviews and observations, the data obtained is more clearly accurate. Based on the results of research, there is a lack of motivation in class VII students at MTS Yati Kamang Mudik. The informants in this study consisted of 1 core informant, 10 supporting informants, so the total number of informants was 11 people. From the research results, it was found that the role of guidance and counseling teachers in motivating students in Class VII MTs Yati Kamang Mudiak through the Independent Learning Curriculum is by reprimanding, advising and ordering students to enter the class. The Role of Guidance and Guidance Teachers in Motivating Class VII Students of MTs Yati Kamang Mudiak Through the Independent Learning Curriculum, namely:. 1). Improving student learning achievement. 2). Help solve problems faced by students. 3). Helps identify and improve students' abilities. 4) as a mediator. 5). Give students motivation to learn. 7). Provide assistance to other teachers.